ON NEW APPROACH TO ENVIRONMENTAL DAMAGES ESTIMATION UNDER SUSTAINABLE DEVELOPMENT CONCEPT - Vladimir N. Kurdyukov (Advanced Engineering Research, 2012)
The theoretical basics of the pollution damage reduction are considered. Some estimation methods of the emissions damage are analyzed. The approach to the emissions damage evaluation based on the assessment of costs for forming the ecosystem elements, which have a population carrying capacity sufficient for preventing adverse consequences for the population health, natural and tangible objects, is offered.